PECULARITIES OF THE PROFESSIONAL DIALOGUE MEDIATED BY MODERN MEANS OF TELECOMMUNICATION IN THE PROCESS OF TRAINING FUTURE SPECIALISTS IN ECONOMICS - Tetiana V. Kramarenko (Вісник Університету імені Альфреда Нобеля. Серія Педагогіка і психология, 2021)
The article considers and analyzes the features of professional dialogue mediated by means of information and communication technologies in the training of future economic specialists, the main aspects of the use of mediated dialogue in foreign language teaching. Possibilities of communication mediated by information and communication technologies in the process of learning a foreign language by future specialists in economics are considered. The concept of indirect dialogue based on the analysis of existing approaches of scientists to the problem of using information and communication technologies in the process of training future specialists in economics is revealed. Features of dialogue on the basis of Internet technologies are considered. The classification of types of educational dialogue by means of information technologies on pedagogical orientation is given. The issues of culture and ethics of behavior in the information space during the dialogue mediated by modern means of telecommunications, the use of information presented in information networks are substantiated. Based on the analysis of various approaches to the use of computer communication, the essence of this concept is revealed and the ways of its further use in the training of economics specialists are substantiated. The requirements for professional dialogue mediated by computer means are presented. The system of conditions that promote the implementation of intersubject dialogue, taking into account the specifics of its organization in the computer environment, ie: providing internal and external dialogue of the student; psychological comfort of students in dialogic interaction; depth of dialogue; compliance of the purpose of the dialogue with the motive of the student’s entry into it; dialogic content of educational material; readiness of the learning situation and its participants for dialogue; the expediency of including in the educational process of computer-mediated dialogue; attitude to the computer as a quasi-subject of dialogue. It was found that it is advisable to combine modern information and communication technologies with traditional learning technologies in the learning process. It is proved that the electronic environment creates conditions for autonomous, individual-cooperative, joint activity of students, promoting the formation of a culture of professional dialogue, personal, communicative self-development, and the use of information and communication technologies opens new prospects for professional training of future economists.